Clonal Variation in Basic Density and Anatomical Properties of Eucalyptus tereticornis - Four to Five Years - Vijendra Rao, R.; Shashikala, S.; Sreevani, P.; Kothiyal, V. (Indian Forester, 2005)
The basic density and anatomical properties of five clones of Eucalyptus tereticornis developed by ITC Bhadrachalam are reported. Tbe five clones represented by four trees each, of 4-5 year old were from Sarapaka demonstration plot, Andhra Pradesh, India. Intra-clonal variation was significant in basic density, vessel diameter, vessel element length, fibre length, fibre diameter, fibre wall thickness, while variation in tissue proportions were non-significant. However, inter-clonal variation was significant for all the parameters. Basic density was positively correlated with vessel diameter and percentage of rays, while girth had a negative influence on fibre diameter and fibre wall thickness. Fibre length, fibre diameter and fibre lumen diameter were positively inter-correlated, while negative correlations were observed among the tissue proportions. Vessel diameter was also correlated positively with ray percentage and negatively with vessel percentage. All these correlations are suggestive of spatial adjustments in quantitative characteristics among different cell types.